The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1964
DOI: 10.1577/1548-8659(1964)93[27:eotoio]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ten Organic Insecticides on Two Species of Stonefly Naiads

Abstract: Two species of stonefly naiads were exposed to the chlorinated hydrocarbons DDT, aldrin, dieldrin, and endrin and to the organic phosphates parathion, malathion, guthion, Dylox, Di‐Syston, and Bayer‐29493. After the introduction of the pesticide, tests were run for 96 hours with observations made after each 24‐hour period. There was a definite increase in mortality for both Pteronarcys californica and Acroneuria pacifica with increasing exposure time. Higher concentrations of insecticides produced higher death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1966
1966
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A second limitation is that sensitivity of the test organisms is size-(age-) dependent. This limitation is not unique to our method, having been shown in other studies [9,27,33,34]. This underscores the need to utilize small instars in testing whenever possible.…”
Section: Discussionmentioning
confidence: 74%
“…A second limitation is that sensitivity of the test organisms is size-(age-) dependent. This limitation is not unique to our method, having been shown in other studies [9,27,33,34]. This underscores the need to utilize small instars in testing whenever possible.…”
Section: Discussionmentioning
confidence: 74%
“…However, other situations may arise in which exposure to pesticide is prolonged, e.g., runoff of pesticide from treated agricultural land, and accordingly the scope of laboratory tests must be extended to allow for this. Short exposures alone, such as those adopted in the present study, may provide only part of the story, and there is already evidence from laboratory work on dragonfly naiads (Muirhead-Thomson 1973) and plecopteran nymphs (Jensen and Gaufin 1964) that 24-and 48-h periods of exposure may reveal generic or specific differences in reaction that are not evident at shorter periods of l h or less. An extended range of test temperatures is also desirable as it has been shown that with trichopteran larvae for example, in static tests, that chlorinated hydrocarbons are more toxic at 10°C than at 2VC, while the reverse is true for organophosphates (Fredeen 1972).…”
Section: Discussionmentioning
confidence: 74%
“…American work with stonefly (Plecoptera) naiads, in static water tests, has shown that within the same species there are wide differences in reaction to different chemical pesticides, much the same as has been established for freshwater fish (Jensen & Gaufin, 1960, 1964aGaufin et al, 1965;Saunders & Cope, 1968).…”
Section: Discussionmentioning
confidence: 81%